Alterations of the gastric stump and not resected stomach mucosa after truncal vagotomy in rats - Rodrigues,Paulo Antônio (2014)
PURPOSE:To evaluate morphological changes of the gastric stump and not resected stomach mucosa after the completion of truncal vagotomy.METHODS:Eighty male Wistar rats were divided into four groups: CT, TV, RY and RYTV. In CT group, abdominal viscera were manipulated and the abdominal cavity was closed, in TV vagal trunks were isolated and sectioned, in RY a partial Roux-en-Y gastrectomy was performed and in RYTV the vagal trunks were sectioned and a partial Roux-en-Y gastrectomy was performed. At the 54th week after surgery, the rats were euthanized. The findings were submitted to histological analyses.RESULTS:None macroscopic or histological alterations in groups TV and CT was observed. Specimens from RY and RYTV groups did not show alterations in the gastric stump mucosa. At the jejunal side of the gastroenterostomy we found shallow ulcerative lesions always single, well-defined and with variable diameter 3 to 6 mm, six times in the RY group and none in the RYTV group (RY>RYTV, p=0.008). Neoplastic or preneoplastic lesions were not diagnosed in all groups.CONCLUSION: Truncal vagotomy is a safe and non-carcinogenic method in not resected and partially resected stomach.